Sulfide-based solid electrolyte, electric storage element, and method for producing sulfide-based solid electrolyte

JP7631770B2Active Publication Date: 2025-02-19GS YUASA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2020204598
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-12-09
Publication Date
2025-02-19
Estimated Expiration
2040-12-09

AI Technical Summary

Benefits of technology

【0008】 本発明の一側面に係る硫化物系固体電解質によれば、イオン伝導性に優れる硫化物系固体電解質を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007631770000002
    Figure 0007631770000002
  • Figure 0007631770000003
    Figure 0007631770000003
  • Figure 0007631770000004
    Figure 0007631770000004
Patent Text Reader

Abstract

To provide a sulfide-based solid electrolyte having excellent ionic conductivity and a power storage element.SOLUTION: A sulfide-based solid electrolyte according to an embodiment of the present invention has a crystal structure that can be attributed to a space group F-43m and contains lithium, phosphorus, sulfur, chlorine, and fluorine. Preferably, the ratio of the content of the fluorine to the total content of the chlorine and the fluorine is 0.075 or less in terms of molar ratio.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a sulfide-based solid electrolyte and an electric storage device. [Background technology]

[0002] Lithium ion secondary batteries are widely used in electronic devices such as personal computers and communication terminals, automobiles, etc., due to their high energy density. The lithium ion secondary battery generally has a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte interposed between the electrodes, and is configured to charge and discharge by transferring lithium ions between the electrodes. In addition, capacitors such as lithium ion capacitors are also widely used as storage elements other than lithium ion secondary batteries.

[0003] In recent years, in order to improve the safety of non-aqueous electrolyte secondary batteries, electricity storage elements have been proposed that use sulfide-based solid electrolytes or the like as the non-aqueous electrolyte instead of liquid electrolytes such as organic solvents (see Patent Document 1). Compared with oxide-based sulfide-based solid electrolytes, such sulfide-based solid electrolytes have the properties of high electrical conductivity and excellent moldability. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2000-340257 A Summary of the Invention [Problem to be solved by the invention]

[0005] However, for energy storage elements used in hybrid electric vehicles (hereinafter also referred to as "HEVs") and hybrid industrial machinery (heavy machinery, construction machinery, etc.), there is a demand for sulfide-based solid electrolyte materials with further improved ionic conductivity.

[0006] The present invention has been made in light of the above circumstances, and an object of the present invention is to provide a sulfide-based solid electrolyte having excellent ion conductivity. [Means for solving the problem]

[0007] One aspect of the present invention is a sulfide-based solid electrolyte that has a crystal structure that can be assigned to the space group F-43m and contains lithium, phosphorus, sulfur, chlorine and fluorine. Effect of the Invention

[0008] According to one aspect of the present invention, a sulfide-based solid electrolyte having excellent ion conductivity can be provided. [Brief description of the drawings]

[0009] [Figure 1] FIG. 1 is a schematic cross-sectional view of an all-solid-state battery which is one embodiment of the energy storage element of the present invention. [Diagram 2] FIG. 2 is a schematic diagram showing an energy storage device formed by assembling a plurality of energy storage elements according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a graph showing the temperature dependence of ionic conductivity in the sulfide-based solid electrolytes of Examples 1 to 3 and Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] A sulfide-based solid electrolyte according to one aspect of the present invention has a crystal structure that can be assigned to the space group F-43m, and contains lithium, phosphorus, sulfur, chlorine, and fluorine.

[0011] The sulfide-based solid electrolyte has a crystal structure that can be assigned to the space group F-43m, and contains lithium, phosphorus, sulfur, chlorine, and fluorine, and thus has excellent ion conductivity. The reason for this is unclear, but the following reasons are speculated. The sulfide-based solid electrolyte is an Argyrodite-type sulfide-based solid electrolyte that has a crystal structure that can be assigned to the space group F-43m and contains lithium, phosphorus, sulfur, and chlorine, which is a halogen, and is thought to have a structure in which some of the chlorine ions are replaced with fluorine ions. In this way, some of the chlorine ions are replaced with fluorine ions, which have a smaller ionic radius than the chlorine ions, and the diffusion path of the lithium ions is expanded. In addition, it is thought that by including ions with a relatively small ionic radius, such as chlorine ions and fluorine ions, as halogen ions, the crystal lattice becomes smaller, making the crystal structure more stable. As a result, it is speculated that the lithium ion conductivity of the sulfide-based solid electrolyte is improved.

[0012] In the sulfide-based solid electrolyte, the molar ratio of the fluorine content to the total content of the chlorine and fluorine is preferably 0.075 or less. By making the molar ratio of the fluorine content 0.075 or less, the ionic conductivity of the sulfide-based solid electrolyte can be further increased.

[0013] It is preferable that the sulfide-based solid electrolyte has a first diffraction peak and a second diffraction peak in an X-ray diffraction measurement using CuKα radiation, the first diffraction peak being in the range of 2θ=15.45°±0.05°, and the second diffraction peak being in the range of 2θ=17.85°±0.05°. When the positions of the first diffraction peak and the second diffraction peak in the X-ray diffraction measurement of the sulfide-based solid electrolyte are in the above ranges, the ionic conductivity of the sulfide-based solid electrolyte can be further increased.

[0014] An electric storage element according to another aspect of the present invention contains the sulfide-based solid electrolyte.

[0015] The energy storage element according to another aspect of the present invention contains the sulfide-based solid electrolyte, and therefore has excellent ion conductivity and excellent charge / discharge performance, such as high-rate charge / discharge performance.

[0016] Hereinafter, embodiments of the sulfide-based solid electrolyte and the electricity storage element according to the present invention will be described in detail.

[0017] <Sulfide solid electrolyte> The sulfide-based solid electrolyte according to one embodiment of the present invention is a sulfide-based solid electrolyte having a crystal structure that can be assigned to the space group F-43m and containing lithium, phosphorus, sulfur, chlorine and fluorine. The sulfide-based solid electrolyte is a cubic crystal and has an Argyrodite-type crystal structure. In the sulfide-based solid electrolyte, a part of the chloride ions in the Argyrodite-type sulfide-based solid electrolyte is replaced with a fluorine ion having a smaller ionic radius than the chloride ion, thereby expanding the diffusion path of the lithium ion. Therefore, the sulfide-based solid electrolyte has excellent ionic conductivity. The sulfide-based solid electrolyte can be used for any application requiring excellent ionic conductivity. In particular, the sulfide-based solid electrolyte is preferably used for a lithium ion storage element.

[0018] In the sulfide-based solid electrolyte, the upper limit of the ratio of the fluorine content to the total content of the chlorine and fluorine is preferably 0.075 in molar ratio. The lower limit of the fluorine content is preferably more than 0 in molar ratio, more preferably 0.025. When the fluorine content ratio is equal to or less than the upper limit or equal to or more than the lower limit, a crystal phase with high ionic conductivity is easily precipitated, and ionic conductivity can be further increased.

[0019] The sulfide-based solid electrolyte is, for example, Li6PS5Cl 1-x F x (x is a number equal to or greater than 0.025 and equal to or less than 0.075.)

[0020] The sulfide-based solid electrolyte has a diffraction pattern that can be assigned to the space group F-43m in an X-ray diffraction measurement using CuKα radiation. The sulfide-based solid electrolyte preferably has a first diffraction peak and a second diffraction peak in an X-ray diffraction measurement. In addition, the first diffraction peak preferably exists in a range of 2θ=15.45°±0.05° and the second diffraction peak preferably exists in a range of 2θ=17.85°±0.05° in an X-ray diffraction measurement using CuKα radiation. When the positions of the first diffraction peak and the second diffraction peak in an X-ray diffraction measurement using CuKα radiation of the sulfide-based solid electrolyte are within the above ranges, the ion conductivity can be further increased.

[0021] The X-ray diffraction measurement using the CuKα ray is carried out according to the following procedure. The solid electrolyte powder to be measured is filled into an airtight sample holder for X-ray diffraction measurement in an argon atmosphere with a dew point of -50°C or less. Powder X-ray diffraction measurement is carried out using an X-ray diffractometer (Rigaku's "MiniFlex II"). The radiation source is CuKα ray, the tube voltage is 30 kV, the tube current is 15 mA, and the diffracted X-ray is passed through a 30 μm thick Kβ filter and detected by a high-speed one-dimensional detector (model number: D / teX Ultra 2). The sampling width is 0.01°, the scan speed is 5° / min, the divergence slit width is 0.625°, the receiving slit width is 13 mm (OPEN), and the scattering slit width is 8 mm.

[0022] The upper limit of the intensity ratio of the first diffraction peak to the second diffraction peak is preferably 2.11. On the other hand, the lower limit of the intensity ratio of the first diffraction peak is preferably 1.00, more preferably 1.40, and even more preferably 1.70. When the intensity ratio of the first diffraction peak to the second diffraction peak is equal to or less than the upper limit or equal to or more than the lower limit, the lithium ion conductivity of the sulfide-based solid electrolyte is improved. Although the reason is unclear, the following reason is presumed. In a crystal structure that can be assigned to the space group F-43m in which some of the chloride ions are replaced by fluorine ions, there is no clear correlation between the content (substitution amount) of fluorine ions and the intensity ratio of the first diffraction peak to the second diffraction peak, but the intensity ratio is smaller than 2.12 of the peak of a sulfide solid electrolyte in which the chloride ions are not replaced by fluorine ions. In addition, the sulfide-based solid electrolyte contains some chlorine ions substituted with fluorine ions, but the crystal orientation is different from that of a composition in which some bromine ions, which are the same halogen ions, are substituted with fluorine ions or some iodine ions are substituted with fluorine ions, and the intensity ratio of the first diffraction peak to the second diffraction peak is greater than 1. Therefore, when the intensity ratio of the peaks is equal to or less than the upper limit or equal to or more than the lower limit, the composition has chlorine ions substituted with fluorine ions in an appropriate range, and as a result, it is believed that the lithium ion conductivity of the sulfide-based solid electrolyte is improved.

[0023] The lower limit of the ionic conductivity of the sulfide-based solid electrolyte at 25°C is 2.19 × 10 -3 S / cm is preferred, 2.26×10 -3 S / cm is more preferable, 2.63×10 -3 When the sulfide-based solid electrolyte has an ionic conductivity at 25° C. of not less than the above value, the charge / discharge performance, such as the high-rate charge / discharge performance, of the energy storage device can be improved.

[0024] The ionic conductivity of the sulfide-based solid electrolyte is determined by measuring the AC impedance using the following method. In an argon atmosphere with a dew point of -50°C or less, 120 mg of sample powder is placed in a powder molder with an inner diameter of 10 mm, and then uniaxially pressed at 50 MPa or less using a hydraulic press. After releasing the pressure, 120 mg of SUS (Steel Use Stainless) 316L powder is placed on the upper surface of the sample as a current collector, and then uniaxially pressed at 50 MPa or less using a hydraulic press again. Next, 120 mg of SUS316L powder is placed on the lower surface of the sample as a current collector, and then uniaxially pressed at 360 MPa for 5 minutes to obtain a pellet for measuring ionic conductivity. The pellet for measuring ionic conductivity is inserted into a HS cell manufactured by Hosen Co., Ltd., and AC impedance is measured at a specified temperature. The measurement conditions are an applied voltage amplitude of 20 mV and a frequency range of 1 MHz to 100 mHz.

[0025] The shape of the sulfide-based solid electrolyte is not particularly limited, and is usually granular, lumpy, or the like. When the sulfide-based solid electrolyte is granular, the lower limit of the average particle size is, for example, 0.5 μm, preferably 0.7 μm, and more preferably 1 μm. On the other hand, the upper limit is, for example, 10 μm, preferably 7 μm, and more preferably 3 μm. When the average particle size of the sulfide-based solid electrolyte is equal to or greater than the lower limit or equal to or less than the upper limit, good ion conductivity is exhibited when used in an energy storage element, and thus the discharge capacity can be increased. The term "average particle size" refers to the value (median diameter) at which the volume-based cumulative distribution calculated in accordance with JIS-Z-8819-2 (2001) is 50% based on the particle size distribution measured by a laser diffraction / scattering method for a diluted solution obtained by diluting particles with a solvent in accordance with JIS-Z-8825 (2013). The same applies to the average particle size below. The average particle size of the sulfide-based solid electrolyte is specifically a value measured by the following method. Measurements are performed using a laser diffraction / scattering particle size distribution analyzer (HORIBA's "Partica LA-960"). Ultra-dehydrated heptane is used as the dispersion medium, and the measurement cell is filled with a dispersion liquid in which the particles of the sample to be measured are dispersed in the dispersion medium. A laser beam is irradiated onto this measurement cell, and a scattered light distribution is obtained from the measurement sample. The particle diameter at which the cumulative degree of 50% (D50) obtained from the scattered light distribution is the average particle diameter.

[0026] The sulfide-based solid electrolyte has excellent ion conductivity. The sulfide-based solid electrolyte can be suitably used as an electrolyte for a storage element such as a lithium ion secondary battery, particularly a lithium ion storage element. In particular, the sulfide-based solid electrolyte can be suitably used as an electrolyte for an all-solid-state battery. The sulfide-based solid electrolyte can be used for any of a positive electrode layer, a separator layer, a negative electrode layer, etc. in a storage element.

[0027] <Electricity storage element> As an embodiment of the energy storage element of the present invention, an all-solid-state battery will be specifically described below. The energy storage element 10 shown in FIG. 1 is an all-solid-state battery, and is a secondary battery in which a positive electrode layer 1 and a negative electrode layer 2 are arranged with an isolating layer 3 interposed therebetween. The positive electrode layer 1 has a positive electrode substrate 4 and a positive electrode active material layer 5, and the positive electrode substrate 4 is the outermost layer of the positive electrode layer 1. The negative electrode layer 2 has a negative electrode substrate 7 and a negative electrode active material layer 6, and the negative electrode substrate 7 is the outermost layer of the negative electrode layer 2. In the energy storage element 10 shown in FIG. 1, the negative electrode active material layer 6, the isolating layer 3, the positive electrode active material layer 5, and the positive electrode substrate 4 are laminated in this order on the negative electrode substrate 7.

[0028] The energy storage element 10 contains a sulfide-based solid electrolyte according to an embodiment of the present invention in at least one of the positive electrode layer 1, the negative electrode layer 2, and the separator layer 3. More specifically, the sulfide-based solid electrolyte according to an embodiment of the present invention is contained in at least one of the positive electrode active material layer 5, the negative electrode active material layer 6, and the separator layer 3. Since the energy storage element 10 contains the sulfide-based solid electrolyte having excellent ion conductivity, it has excellent ion conductivity and excellent charge / discharge performance such as high-rate charge / discharge performance.

[0029] The energy storage element 10 may be configured to use a sulfide-based solid electrolyte other than the sulfide-based solid electrolyte according to one embodiment of the present invention. Examples of the other sulfide-based solid electrolyte include sulfide-based solid electrolytes other than the sulfide-based solid electrolyte, oxide-based solid electrolytes, dry polymer electrolytes, gel polymer electrolytes, and pseudo-solid electrolytes, and the sulfide-based solid electrolyte is preferred. In addition, a single layer in the energy storage element 10 may contain a plurality of different sulfide-based solid electrolytes, or each layer may contain a different sulfide-based solid electrolyte.

[0030] Examples of sulfide-based solid electrolytes include Li2S-P2S5, Li2S-P2S5-LiI, Li2S-P2S5-LiCl, Li2S-P2S5-LiBr, Li2S-P2S5-Li2O, Li2S-P2S5-Li2O-LiI, Li2S-P2S5-Li3N, Li2S-SiS2, Li2S-SiS2-LiI, Li2S-SiS2-LiBr, Li2S-SiS2-LiCl, Li2S-SiS2-B2S3-LiI, Li2S-SiS2-P2S5-LiI, Li2S-B2S3, and Li2S-P2S5-Z. m S 2n (where m and n are positive numbers, and Z is Ge, Zn, or Ga.), Li2S-GeS2, Li2S-SiS2-Li3PO4, Li2S-SiS2-Li x MO y (where x and y are positive numbers, and M is P, Si, Ge, B, Al, Ga, or In.) Li 10 GeP2S 12 etc. can be mentioned.

[0031] [Positive electrode layer] The positive electrode layer 1 includes a positive electrode substrate 4 and a positive electrode active material layer 5 laminated on the surface of the positive electrode substrate 4 directly or via an intermediate layer.

[0032] (Positive electrode substrate) The positive electrode substrate 4 is conductive. Whether or not it has "conductivity" is judged by using a volume resistivity of 107 Ω·cm measured in accordance with JIS-H-0505 (1975) as a threshold value. As the material of the positive electrode substrate, metals such as aluminum, titanium, tantalum, stainless steel, etc. or alloys thereof are used. Among these, aluminum or aluminum alloys are preferred from the viewpoints of potential resistance, high conductivity, and cost. As the positive electrode substrate, foil, vapor deposition film, mesh, porous material, etc. can be mentioned, and foil is preferred from the viewpoint of cost. Therefore, aluminum foil or aluminum alloy foil is preferred as the positive electrode substrate. As the aluminum or aluminum alloy, A1085, A3003, A1N30, etc. specified in JIS-H-4000 (2014) or JIS-H4160 (2006) can be exemplified.

[0033] The average thickness of the positive electrode substrate 4 is preferably 3 μm to 50 μm, more preferably 5 μm to 40 μm, further preferably 8 μm to 30 μm, and particularly preferably 10 μm to 25 μm. By setting the average thickness of the positive electrode substrate 4 within the above range, the strength of the positive electrode substrate 4 can be increased, while the energy density per volume of the energy storage element 10 can be increased.

[0034] The intermediate layer is a layer disposed between the positive electrode substrate 4 and the positive electrode active material layer 5. The intermediate layer contains a conductive agent such as carbon particles to reduce the contact resistance between the positive electrode substrate and the positive electrode active material layer. The configuration of the intermediate layer is not particularly limited, and may contain, for example, a binder and a conductive agent.

[0035] (Cathode active material layer) The positive electrode active material layer 5 includes a positive electrode active material. The positive electrode active material layer 5 may include a mixture or a composite including a positive electrode active material and a sulfide-based solid electrolyte. The positive electrode active material layer 5 includes optional components such as a conductive agent, a binder, a thickener, and a filler, as necessary.

[0036] The positive electrode active material can be appropriately selected from known positive electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the positive electrode active material for a lithium ion secondary battery. Examples of the positive electrode active material include lithium transition metal composite oxides having an α-NaFeO2 type crystal structure, lithium transition metal composite oxides having a spinel type crystal structure, polyanion compounds, chalcogen compounds, and sulfur. Examples of the lithium transition metal composite oxides having an α-NaFeO2 type crystal structure include Li[Li x Ni (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Co (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Co (1-x) ]O2(0≦x<0.5), Li[Li x Ni γ Mn (1-x-γ) ]O2(0≦x<0.5, 0<γ<1), Li[Li x Niγ Mn β Co (1-x-γ-β) ]O2(0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), Li[Li x Ni γ Co β Al (1-x-γ-β) ]O2 (0≦x<0.5, 0<γ, 0<β, 0.5<γ+β<1), etc. Lithium transition metal composite oxides with spinel crystal structure include Li x Mn2O4, Li x Ni γ Mn (2-γ) O4, etc. Examples of polyanion compounds include LiFePO4, LiMnPO4, LiNiPO4, LiCoPO4, Li3V2(PO4)3, Li2MnSiO4, Li2CoPO4F, etc. Examples of chalcogen compounds include titanium disulfide, molybdenum disulfide, molybdenum dioxide, etc. Atoms or polyanions in these materials may be partially substituted with atoms or anion species of other elements. The surfaces of these materials may be coated with other materials. In the positive electrode active material layer, one of these materials may be used alone, or two or more may be mixed and used.

[0037] The positive electrode active material is usually in the form of particles (powder). The average particle size of the positive electrode active material is preferably, for example, 0.1 μm or more and 20 μm or less. By setting the average particle size of the positive electrode active material to the above lower limit or more, the positive electrode active material can be easily manufactured or handled. By setting the average particle size of the positive electrode active material to the above upper limit or less, the electronic conductivity of the positive electrode active material layer 5 is improved. When a composite of the positive electrode active material and another material is used, the average particle size of the composite is taken as the average particle size of the positive electrode active material.

[0038] In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, etc. are used. Examples of the pulverization method include a method using a mortar, a ball mill, a sand mill, a vibration ball mill, a planetary ball mill, a jet mill, a counter jet mill, a swirling airflow type jet mill, or a sieve. During pulverization, wet pulverization in the presence of water or an organic solvent such as hexane can also be used. As a classification method, a sieve, an air classifier, etc. are used as necessary for both the dry and wet methods.

[0039] The content of the positive electrode active material in the positive electrode active material layer 5 is preferably 50% by mass to 99% by mass, more preferably 70% by mass to 98% by mass, and even more preferably 80% by mass to 95% by mass. By setting the content of the positive electrode active material within the above range, it is possible to achieve both high energy density and manufacturability of the positive electrode active material layer 5.

[0040] When the positive electrode active material layer 5 contains a sulfide-based solid electrolyte, the content of the sulfide-based solid electrolyte is preferably 1% by mass or more and 50% by mass or less, more preferably 10% by mass or more and 40% by mass or less, and even more preferably 30% by mass or less. By setting the content of the sulfide-based solid electrolyte within the above range, the electric capacity of the storage element 10 can be increased. When the sulfide-based solid electrolyte according to one embodiment of the present invention is used for the positive electrode active material layer 5, the content of the sulfide-based solid electrolyte according to one embodiment of the present invention relative to the total sulfide-based solid electrolyte in the positive electrode active material layer 5 is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and even more preferably substantially 100% by mass.

[0041] The mixture of the positive electrode active material and the sulfide-based solid electrolyte is a mixture prepared by mixing the positive electrode active material and the sulfide-based solid electrolyte by mechanical milling or the like. For example, the mixture of the positive electrode active material and the sulfide-based solid electrolyte can be obtained by mixing a particulate positive electrode active material and a particulate sulfide-based solid electrolyte. Examples of the composite of the positive electrode active material and the sulfide-based solid electrolyte include a composite having a chemical or physical bond between the positive electrode active material and the sulfide-based solid electrolyte, a composite in which the positive electrode active material and the sulfide-based solid electrolyte are physically combined, and the like. The composite is one in which the positive electrode active material and the sulfide-based solid electrolyte are present in one particle, and examples of the composite include one in which the positive electrode active material and the sulfide-based solid electrolyte form an aggregated state, and one in which a film containing the sulfide-based solid electrolyte is formed on at least a part of the surface of the positive electrode active material.

[0042] The conductive agent is not particularly limited as long as it is a material having electrical conductivity. Examples of such conductive agents include carbonaceous materials, metals, conductive ceramics, and the like. Examples of carbonaceous materials include graphite, non-graphitic carbon, graphene-based carbon, and the like. Examples of non-graphitic carbon include carbon nanofibers, pitch-based carbon fibers, carbon black, and the like. Examples of carbon black include furnace black, acetylene black, ketjen black, and the like. Examples of graphene-based carbon include graphene, carbon nanotubes (CNT), fullerene, and the like. Examples of the conductive agent include powder and fiber. As the conductive agent, one of these materials may be used alone, or two or more of them may be mixed and used. These materials may also be used in combination. For example, a material in which carbon black and CNT are combined may be used. Among these, carbon black is preferable from the viewpoint of electronic conductivity and coatability, and acetylene black is preferable among them.

[0043] The content of the conductive agent in the positive electrode active material layer 5 is preferably from 1 mass % to 10 mass %, and more preferably from 3 mass % to 9 mass %. By setting the content of the conductive agent in the above range, the energy density of the electricity storage element 10 can be increased.

[0044] Examples of binders include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), etc.), polyethylene, polypropylene, polyacrylic, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.

[0045] The binder content in the positive electrode active material layer 5 is preferably from 1 mass % to 10 mass %, and more preferably from 3 mass % to 9 mass %. By setting the binder content in the above range, the positive electrode active material can be stably maintained.

[0046] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC), methyl cellulose, etc. When the thickener has a functional group that reacts with lithium or the like, this functional group may be deactivated in advance by methylation or the like.

[0047] The filler is not particularly limited. Examples of the filler include polyolefins such as polypropylene and polyethylene, inorganic oxides such as silicon dioxide, alumina, titanium dioxide, calcium oxide, strontium oxide, barium oxide, magnesium oxide, and aluminosilicates, hydroxides such as magnesium hydroxide, calcium hydroxide, and aluminum hydroxide, carbonates such as calcium carbonate, poorly soluble ion crystals such as calcium fluoride, barium fluoride, and barium sulfate, nitrides such as aluminum nitride and silicon nitride, and mineral resource-derived substances such as talc, montmorillonite, boehmite, zeolite, apatite, kaolin, mullite, spinel, olivine, sericite, bentonite, and mica, or artificial products thereof.

[0048] The positive electrode active material layer 5 may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Nb, and W as components other than the positive electrode active material, conductive agent, binder, thickener, and filler.

[0049] The average thickness of the positive electrode active material layer 5 is preferably 30 μm or more and 1,000 μm or less, and more preferably 60 μm or more and 500 μm or less. By setting the average thickness of the positive electrode active material layer 5 to be equal to or more than the above lower limit, it is possible to obtain a storage element 10 having a high energy density. By setting the average thickness of the positive electrode active material layer 5 to be equal to or less than the above upper limit, it is possible to reduce the size of the storage element 10. The average thickness of the positive electrode active material layer 5 is the average value of thicknesses measured at any five positions. The same applies to the average thicknesses of the negative electrode active material layer 6 and the separator layer 3 described later.

[0050] [Negative electrode layer] The negative electrode layer 2 has a negative electrode substrate 7 and a negative electrode active material layer 6 disposed directly or via an intermediate layer on the negative electrode substrate 7. The configuration of the intermediate layer is not particularly limited and can be selected from the configurations exemplified for the positive electrode layer 1, for example.

[0051] (Negative electrode substrate) The negative electrode substrate 7 is conductive. Metals such as copper, nickel, stainless steel, nickel-plated steel, and aluminum, or alloys thereof, carbonaceous materials, and the like are used as the material of the negative electrode substrate 7. Among these, copper or copper alloys are preferred. Examples of the negative electrode substrate 7 include foils, vapor deposition films, meshes, and porous materials, and foils are preferred from the viewpoint of cost. Therefore, copper foil or copper alloy foil is preferred as the negative electrode substrate. Examples of copper foil include rolled copper foil and electrolytic copper foil.

[0052] The average thickness of the negative electrode substrate 7 is preferably 2 μm to 35 μm, more preferably 3 μm to 30 μm, further preferably 4 μm to 25 μm, and particularly preferably 5 μm to 20 μm. By setting the average thickness of the negative electrode substrate 7 within the above range, the strength of the negative electrode substrate 7 can be increased, while the energy density per volume of the energy storage element 10 can be increased.

[0053] (Negative electrode active material layer) The negative electrode active material layer 6 includes a negative electrode active material. The negative electrode active material layer 6 may include a mixture or a composite including a negative electrode active material and a sulfide-based solid electrolyte. The negative electrode active material layer 6 includes optional components such as a conductive agent, a binder, a thickener, and a filler as necessary. The optional components such as a conductive agent, a binder, a thickener, and a filler can be selected from the materials exemplified for the positive electrode above.

[0054] The negative electrode active material layer 6 may contain typical nonmetallic elements such as B, N, P, F, Cl, Br, and I, typical metallic elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, Sn, Sr, and Ba, and transition metallic elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W as components other than the negative electrode active material, conductive agent, binder, thickener, and filler.

[0055] The negative electrode active material can be appropriately selected from known negative electrode active materials. A material capable of absorbing and releasing lithium ions is usually used as the negative electrode active material for lithium ion secondary batteries. Examples of the negative electrode active material include metal Li; metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide, Ti oxide, and Sn oxide; Li4Ti5O 12 , LiTiO 2、 Examples of the material include titanium-containing oxides such as TiNb2O7, polyphosphate compounds, silicon carbide, and carbon materials such as graphite and non-graphitic carbon (easily graphitized carbon or non-graphitizable carbon). Among these materials, graphite and non-graphitic carbon are preferred. In the negative electrode active material layer, one of these materials may be used alone, or two or more of them may be used in combination.

[0056] "Graphite" refers to a material that has an average lattice spacing (d 002 ) is 0.33 nm or more and less than 0.34 nm. Examples of graphite include natural graphite and artificial graphite. Artificial graphite is preferred from the viewpoint of availability of materials with stable physical properties.

[0057] "Non-graphitic carbon" refers to carbon that has an average lattice spacing (d 002 ) is 0.34 nm or more and 0.42 nm or less. Examples of non-graphitizable carbon include non-graphitizable carbon and graphitizable carbon. Examples of non-graphitizable carbon include resin-derived materials, petroleum pitch or petroleum pitch-derived materials, petroleum coke or petroleum coke-derived materials, plant-derived materials, and alcohol-derived materials.

[0058] Here, the "discharged state" refers to a state in which the negative electrode active material carbon material is discharged so that lithium ions that can be absorbed and released during charging and discharging are sufficiently released. For example, in a single-electrode battery using a negative electrode containing a carbon material as a negative electrode active material as a working electrode and metallic Li as a counter electrode, the state is one in which the open circuit voltage is 0.7 V or more.

[0059] "Non-graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.36 nm or more and 0.42 nm or less.

[0060] "Graphitizable carbon" means the above d 002 This refers to carbon materials with a particle size of 0.34 nm or more and less than 0.36 nm.

[0061] The negative electrode active material is usually a particle (powder). The average particle size of the negative electrode active material can be, for example, 1 nm or more and 100 μm or less. When the negative electrode active material is a carbon material, a titanium-containing oxide, or a polyphosphate compound, the average particle size may be 1 μm or more and 100 μm or less. When the negative electrode active material is Si, Sn, Si oxide, Sn oxide, or the like, the average particle size may be 1 nm or more and 1 μm or less. By setting the average particle size of the negative electrode active material to the above lower limit or more, the negative electrode active material can be easily manufactured or handled. By setting the average particle size of the negative electrode active material to the above upper limit or less, the electronic conductivity of the active material layer is improved. In order to obtain powder with a predetermined particle size, a pulverizer, a classifier, or the like is used. The pulverization method and the powder classification method can be selected from, for example, the methods exemplified for the positive electrode. When the negative electrode active material is a metal such as metallic Li, the negative electrode active material may be in the form of a foil.

[0062] The content of the negative electrode active material in the negative electrode active material layer 6 is preferably 60% by mass or more and 99% by mass or less, and more preferably 90% by mass or more and 98% by mass or less. By setting the content of the negative electrode active material within the above range, it is possible to achieve both a high energy density and manufacturability of the negative electrode active material layer 6.

[0063] When the negative electrode active material layer 6 contains a sulfide-based solid electrolyte, the content of the sulfide-based solid electrolyte is preferably 1% by mass or more and 40% by mass or less, more preferably 10% by mass or more and 30% by mass or less, and even more preferably 20% by mass or less. By setting the content of the sulfide-based solid electrolyte within the above range, the electric capacity of the storage element 10 can be increased. When the sulfide-based solid electrolyte according to one embodiment of the present invention is used for the negative electrode active material layer 6, the content of the sulfide-based solid electrolyte according to one embodiment of the present invention relative to the total sulfide-based solid electrolyte in the negative electrode active material layer 6 is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and even more preferably substantially 100% by mass.

[0064] The mixture or composite of the negative electrode active material and the sulfide-based solid electrolyte may be the mixture or composite of the positive electrode active material and the sulfide-based solid electrolyte described above, in which the positive electrode active material is replaced with the negative electrode active material.

[0065] The average thickness of the negative electrode active material layer 6 is preferably 30 μm or more and 1,000 μm or less, and more preferably 60 μm or more and 500 μm or less. By setting the average thickness of the negative electrode active material layer 6 to be equal to or more than the above lower limit, it is possible to obtain an energy storage element 10 having a high energy density. By setting the average thickness of the negative electrode active material layer 6 to be equal to or less than the above upper limit, it is possible to reduce the size of the energy storage element 10.

[0066] [Isolation layer] The isolating layer 3 contains a solid electrolyte. As the solid electrolyte contained in the isolating layer 3, in addition to the sulfide-based solid electrolyte according to one embodiment of the present invention described above, various solid electrolytes exemplified in the positive electrode active material layer 5 can be used, and among them, it is preferable to use a sulfide-based solid electrolyte. The content of the solid electrolyte in the isolating layer 3 is preferably 70% by mass or more, more preferably 90% by mass or more, even more preferably 99% by mass or more, and even more preferably substantially 100% by mass. In addition, when the sulfide-based solid electrolyte according to one embodiment of the present invention is used in the isolating layer 3, the content of the sulfide-based solid electrolyte according to one embodiment of the present invention in the total solid electrolyte in the isolating layer 3 is preferably 50% by mass or more, more preferably 70% by mass or more, even more preferably 90% by mass or more, and even more preferably substantially 100% by mass.

[0067] The isolating layer 3 may contain optional components such as a binder, a thickener, a filler, etc. The optional components such as the binder, the thickener, the filler, etc. can be selected from the materials exemplified for the positive electrode active material layer 5.

[0068] The average thickness of the isolating layer 3 is preferably 1 μm or more and 50 μm or less, and more preferably 3 μm or more and 20 μm or less. By setting the average thickness of the isolating layer 3 to be equal to or more than the above lower limit, it is possible to reliably insulate the positive electrode layer 1 from the negative electrode layer 2. By setting the average thickness of the isolating layer 3 to be equal to or less than the above upper limit, it is possible to increase the energy density of the energy storage element 10.

[0069] The shape of the energy storage element of this embodiment is not particularly limited, and examples thereof include a cylindrical battery, a square battery, a flat battery, a coin battery, and a button battery.

[0070] [Configuration of the power storage device] The energy storage element of this embodiment can be mounted as an energy storage device formed by assembling a plurality of energy storage elements 1 in a power source for an automobile such as an electric vehicle (EV), a hybrid vehicle (HEV), or a plug-in hybrid vehicle (PHEV), a power source for electronic devices such as a personal computer or a communication terminal, or a power storage power source, etc. In this case, it is sufficient that the technology of the present invention is applied to at least one energy storage element included in the energy storage device. 2 shows an example of an energy storage device 30 in which energy storage units 20, each of which is an assembly of two or more electrically connected energy storage elements 10, are further assembled. The energy storage device 30 may include a bus bar (not shown) that electrically connects two or more energy storage elements 10, a bus bar (not shown) that electrically connects two or more energy storage units 20, and the like. The energy storage units 20 or the energy storage device 30 may include a status monitoring device (not shown) that monitors the status of one or more energy storage elements.

[0071] [Method of manufacturing sulfide-based solid electrolyte] Although the method for producing a sulfide-based solid electrolyte according to one embodiment of the present invention is not particularly limited, the following method is preferable. That is, the method for producing a sulfide-based solid electrolyte according to one embodiment of the present invention preferably includes preparing a composition containing lithium, phosphorus, sulfur, chlorine and fluorine (preparation step), reacting the composition to obtain an intermediate (reaction step), and heating the intermediate (heating step).

[0072] (preparation process) In this process, a composition containing lithium, phosphorus, sulfur, chlorine and fluorine is prepared. The composition is usually a mixture of two or more compounds containing at least one element selected from the group consisting of lithium, phosphorus, sulfur, chlorine and fluorine. The composition (mixture) may contain the elements lithium, phosphorus, sulfur, chlorine and fluorine. Two or more elements selected from the group consisting of lithium, phosphorus, sulfur, chlorine and fluorine may be contained in one compound. For example, an example of a compound containing lithium and sulfur is Li2S, which will be described later, an example of a compound containing phosphorus and sulfur is P2S5, which will be described later, and an example of a compound containing lithium and chlorine is LiCl, which will be described later.

[0073] Examples of the compound containing lithium include Li2S and metallic lithium. In addition, LiCl, which will be described later, may be used. Among these, Li2S is preferable. The compound containing lithium may be used alone or in combination of two or more.

[0074] An example of the phosphorus-containing compound is P2S5, etc. The phosphorus-containing compound may be used alone or in combination of two or more.

[0075] Examples of compounds containing sulfur include Li2S and P2S. 5、 Elemental sulfur and the like are exemplified. Among these, Li2S and P2S5 are preferred. The sulfur-containing compounds and the like may be used alone or in combination of two or more.

[0076] An example of the chlorine-containing compound is LiCl. The chlorine-containing compound may be used alone or in combination of two or more.

[0077] An example of the fluorine-containing compound is LiF. The chlorine-containing compounds may be used alone or in combination of two or more.

[0078] For example, the composition is preferably a mixture of Li2S, P2S5, LiCl and LiF.

[0079] The specific contents and preferred contents of each element (lithium, phosphorus, sulfur, chlorine, and fluorine) in the above composition are the same as the preferred contents of each element (lithium, phosphorus, sulfur, chlorine, and fluorine) in the sulfide-based solid electrolyte according to one embodiment of the present invention described above.

[0080] (Reaction process) In this process, the composition containing lithium, phosphorus, sulfur, chlorine and fluorine is reacted by, for example, mechanical milling to obtain an intermediate. Note that the means for obtaining the intermediate is not limited to this, and it may be obtained by other methods. For example, instead of mechanical milling, a melt quenching method or the like may be performed.

[0081] Mechanical milling may be either dry or wet, but wet is preferred because it can mix the raw material compounds more uniformly. Mechanical milling includes, for example, a container-driven mill, a media-agitating mill, milling with a high-speed rotary grinder, a roller mill, a jet mill, etc. Container-driven mills include, for example, a rotary mill, a vibration mill, a planetary mill, etc. Media-agitating mills include, for example, an attritor, a bead mill, etc. High-speed rotary grinder milling includes, for example, a hammer mill, a pin mill, etc. Among these, a container-driven mill is preferred, and a planetary mill is particularly preferred.

[0082] The intermediate obtained in the reaction step may have a crystalline structure, but is preferably a so-called sulfide glass. "Sulfide glass" refers to a sulfide-based solid electrolyte containing an amorphous structure. When the intermediate is sulfide glass, it is possible to obtain a sulfide-based solid electrolyte with less stable crystalline phases such as Li2S and with each element being highly dispersed.

[0083] (Heating process) In this step, the intermediate is heated (heat-treated). As a result, at least a part of the intermediate is crystallized, and the target sulfide-based solid electrolyte is obtained. The heating (heat treatment) may be performed under a reduced pressure atmosphere or an inert gas atmosphere. The heating temperature range is preferably, for example, 160°C or higher and lower than 260°C, more preferably 180°C or higher and 255°C or lower, even more preferably 200°C or higher and 250°C or lower, and even more preferably 220°C or higher. By setting the heating temperature within the above range, crystallization progresses sufficiently, and a sulfide-based solid electrolyte with higher ion conductivity is obtained.

[0084] [Method of manufacturing the energy storage element] The method for producing an electric storage element according to an embodiment of the present invention can be performed by a generally known method, except that the sulfide-based solid electrolyte according to an embodiment of the present invention is used to prepare at least one of the positive electrode layer, the separator layer, and the negative electrode layer. Specifically, the method for producing an electric storage element according to an embodiment of the present invention includes, for example, (1) preparing a positive electrode mixture, (2) preparing a separator layer material, (3) preparing a negative electrode mixture, and (4) stacking the positive electrode layer, the separator layer, and the negative electrode layer. Each step will be described in detail below.

[0085] (1) Positive electrode mixture preparation process In this step, a positive electrode mixture for forming a positive electrode layer (positive electrode active material layer) is usually prepared. The method for preparing the positive electrode mixture is not particularly limited and can be appropriately selected according to the purpose. For example, a mechanical milling method for the material of the positive electrode mixture, compression molding of the positive electrode active material, sputtering using a target material of the positive electrode active material, etc. can be mentioned. When the positive electrode mixture contains a mixture or composite containing a positive electrode active material and a sulfide-based solid electrolyte, this step can include, for example, mixing the positive electrode active material and the sulfide-based solid electrolyte using a mechanical milling method or the like to prepare a mixture or composite of the positive electrode active material and the sulfide-based solid electrolyte.

[0086] (2) Preparation of materials for the isolation layer In this step, an isolation layer material for forming an isolation layer is usually prepared. When the storage element is a lithium ion storage element, the isolation layer material can be a sulfide-based solid electrolyte. The sulfide-based solid electrolyte as the isolation layer material can be prepared by a conventionally known method. For example, it can be obtained by processing a predetermined material by a mechanical milling method. The isolation layer material may be prepared by heating a predetermined material to a melting temperature or higher by a melt quenching method, melting and mixing the two at a predetermined ratio, and quenching. Other methods for synthesizing the isolation layer material include, for example, a solid phase method in which the material is sealed under reduced pressure and fired, a liquid phase method such as dissolution deposition, a gas phase method (PLD), and firing in an argon atmosphere after mechanical milling. In addition, when the isolation layer material is the sulfide-based solid electrolyte, the isolation layer material is prepared by a method for producing the sulfide-based solid electrolyte.

[0087] (3) Negative electrode mixture preparation process In this step, a negative electrode mixture for forming a negative electrode layer (negative electrode active material layer) is usually prepared. The specific method for preparing the negative electrode mixture is the same as that for the positive electrode mixture. When the negative electrode mixture contains a mixture or composite containing a negative electrode active material and a sulfide-based solid electrolyte, this step may include, for example, mixing the negative electrode active material and the sulfide-based solid electrolyte using a mechanical milling method or the like to prepare a mixture or composite of the negative electrode active material and the sulfide-based solid electrolyte.

[0088] (Lamination process) In this step, for example, a positive electrode layer having a positive electrode substrate and a positive electrode active material layer, an isolation layer, and a negative electrode layer having a negative electrode substrate and a negative electrode active material layer are laminated. In this step, the positive electrode layer, the isolation layer, and the negative electrode layer may be formed in this order, or may be formed in the reverse order, and the order of formation of each layer is not particularly limited. The positive electrode layer is formed, for example, by pressure molding the positive electrode substrate and the positive electrode mixture, the isolation layer is formed by pressure molding the isolation layer material, and the negative electrode layer is formed by pressure molding the negative electrode substrate and the negative electrode mixture. The positive electrode layer, the isolation layer, and the negative electrode layer may be laminated by pressure molding the positive electrode substrate, the positive electrode mixture, the isolation layer material, the negative electrode mixture, and the negative electrode substrate at once. The positive electrode layer and the negative electrode layer may be molded in advance, respectively, and then pressure molded and laminated with the isolation layer.

[0089] [Other embodiments] The present invention is not limited to the above-mentioned embodiment, and can be embodied in various modified and improved forms in addition to the above-mentioned forms. For example, the electric storage element according to the present invention may have layers other than the positive electrode layer, the separator layer, and the negative electrode layer, such as an intermediate layer or an adhesive layer. The electric storage element according to the present invention may contain a liquid in one or more of the layers. The electric storage element according to the present invention may be a capacitor, etc., in addition to the electric storage element being a secondary battery. EXAMPLES

[0090] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples.

[0091] [Examples 1 to 3 and Comparative Examples 1 to 8] The sulfide-based solid electrolytes (Li6PS5Ha) of Examples 1 to 3 and Comparative Examples 1 to 8 were prepared by the following treatment. 1-x F x , Ha is Cl, Br and I.) was synthesized. (preparation process) Li2S (99.98%, Aldrich) and P2S5 (99%, Aldrich) and either LiCl, LiBr or LiI, or a combination of these with LiF, were mixed in a mortar in a glove box with an argon atmosphere having a dew point of -50°C or less to prepare a composition containing lithium, phosphorus, sulfur, and either chlorine, bromine or iodine, or further fluorine. (Reaction process) The above composition was placed in a sealed 80 mL zirconia pot containing 160 g of zirconia balls with a diameter of 4 mm. Mechanical milling was performed using a planetary ball mill (FRITSCH, model number Premium line P-7) at an orbital speed of 370 rpm for 1 hour, followed by a 2-minute break as one cycle, and the above cycle was repeated 25 times to obtain an intermediate. (Heating process) The intermediate was heated (heat treated) at 500° C. for 4 hours in an argon atmosphere to obtain sulfide-based solid electrolytes of Examples 1 to 3 and Comparative Examples 1 to 8 having the compositions shown in Table 1.

[0092] [evaluation] (1) X-ray diffraction analysis X-ray diffraction measurements using CuKα radiation were performed on the sulfide-based solid electrolytes of Examples 1 to 3 and Comparative Examples 1 to 8 by the above-mentioned method. Table 1 shows the positions (2θ) of the first and second diffraction peaks of the Examples and Comparative Examples, as well as the intensity ratios of the first diffraction peak to the second diffraction peak. Note that "-" indicates that no diffraction peak was observed.

[0093] (2) Ionic conductivity (σ) A pellet was prepared by laminating 120 mg of SUS powder layers on both sides of 120 mg of sulfide-based solid electrolyte layers of Examples 1 to 3 and Comparative Examples 1 to 8. Using this pellet, the AC impedance was measured at -30°C, -20°C, -10°C, 0°C, 25°C and 50°C by the above-mentioned method using Bio-Logic's "VMP-300", and the ionic conductivity of the sulfide-based solid electrolyte of each Example and Comparative Example was obtained. Table 1 shows the ionic conductivity at each temperature of the Examples and Comparative Examples. FIG. 3 shows the relationship between the ionic conductivity of the sulfide-based solid electrolyte of Examples 1 to 3 and Comparative Example 1 and the reciprocal of the absolute temperature, and the activation energy obtained from the slope of the straight line.

[0094] [Table 1]

[0095] As shown in Table 1, the sulfide-based solid electrolytes of Examples 1 to 3 containing lithium, phosphorus, sulfur, chlorine and fluorine had good ionic conductivity at each temperature. On the other hand, the sulfide-based solid electrolytes of Comparative Examples 1 to 8 had lower ionic conductivity than Examples 1 to 3.

[0096] The activation energy indicates the degree of temperature dependence of the ionic conductivity of the sulfide solid electrolyte, and for example, a small activation energy indicates a small difference between the ionic conductivity at low temperature and the ionic conductivity at high temperature. As shown in FIG. 3, the sulfide solid electrolytes of Examples 1 to 3 have a small temperature dependence of the ionic conductivity, and therefore a small activation energy. In other words, it can be seen that by adjusting the fluorine content (substitution amount of fluorine) of the sulfide solid electrolyte, the temperature dependence of the ionic conductivity becomes small, and the activation energy becomes small, which tends to result in good ionic conductivity at low temperatures.

[0097] The above results indicate that the sulfide-based solid electrolyte has excellent ionic conductivity, and is therefore suitable for use as a sulfide-based solid electrolyte for storage elements such as all-solid-state batteries. [Explanation of symbols]

[0098] 1 Positive electrode layer 2. Negative electrode layer 3 isolation layer 4. Positive electrode substrate 5 Cathode active material layer 6 Negative electrode active material layer 7. Negative electrode substrate 10 Energy storage element (all-solid-state battery) 20 Energy Storage Unit 30 Energy storage device

Claims

1. It has a crystal structure that can be assigned to space group F-43m, Contains lithium, phosphorus, sulfur, chlorine and fluorine, A sulfide-based solid electrolyte in which the ratio of the content of the fluorine to the total content of the chlorine and the fluorine is 0.075 or less in terms of molar ratio.

2. It has a crystal structure that can be assigned to space group F-43m, Contains lithium, phosphorus, sulfur, chlorine and fluorine, In an X-ray diffraction measurement using CuKα radiation, the crystal has a first diffraction peak and a second diffraction peak, the first diffraction peak being in a range of 2θ=15.45°±0.05°, and the second diffraction peak being in a range of 2θ=17.85°±0.05°, A sulfide-based solid electrolyte, wherein the intensity ratio of the first diffraction peak to the second diffraction peak is 1.40 or more.

3. 3. An electric storage element comprising the sulfide-based solid electrolyte according to claim 1 or 2.

4. Providing a composition containing lithium, phosphorus, sulfur, chlorine and fluorine; reacting the composition to obtain an intermediate; and heating the intermediate. a ratio of the content of the fluorine to the total content of the chlorine and the fluorine in the composition is 0.075 or less in terms of molar ratio.

Citation Information

Patent Citations

  • Lithium secondary battery

    JP2000340257A

  • Sulfide-based solid electrolyte

    JP2015032529A

  • Sulfide-based solid electrolyte for lithium ion battery

    WO2015012042A1

  • Sulfide solid electrolyte

    WO2018047565A1